Effects of resistance exercise on blood glucose level and pregnancy outcome in patients with gestational diabetes mellitus: a randomized controlled trial. Issue 2 (5th April 2022) - Xie, Yaping; Zhao, Huifen; Zhao, Meijing; Huang, Huibin; Liu, Chunhong; Huang, Fengfeng; Wu, Jingjing
Abstract : Introduction: To date, the effects of resistance exercise on diabetes-related parameters (blood glucose level and insulin use) and pregnancy outcome in participants with gestational diabetes mellitus (GDM) have not been compared with those of aerobic exercise. To investigate the effect of resistance exercise versus aerobic exercise on blood glucose level, insulin utilization rate, and pregnancy outcome in patients with GDM. Research design and methods: From December 2019 to December 2020, 100 pregnant women with GDM were selected and divided into a resistance exercise group (49 patients) and an aerobic exercise group (51 patients) randomly. The aerobic exercise group received an aerobic exercise intervention, while the resistance exercise group received a resistance exercise intervention. Both groups received exercise intervention for 50–60 min, 3 times per week, lasting for 6 weeks. In addition, patients in both groups received the same routine care, including personalized dietary intervention, online education, and school courses for pregnant women. Results: The blood glucose level in the resistance exercise group and the aerobic exercise group was lower after the intervention than before the intervention (p<0.05). After the intervention, no significant differences were observed in the fasting blood glucose level, insulin utilization rate, and incidence of adverse pregnancy outcomes between the two groups (p>0.05); however, significant differences were noted in 2-hour postprandial blood glucose level and exercise compliance between the two groups (p<0.05), with the resistance exercise group showing better outcomes than the aerobic exercise group. Conclusions: Resistance exercise is more compliant for pregnant women with GDM than aerobic exercise; hence, it is necessary to popularize resistance exercise in this specific population group. Long-term effects of resistance exercise should be evaluated in future studies. Trial registration number: ChiCTR 1900027929.